TGfU in Basketball Learning: Impacts on Active Engagement and Learning Outcomes of Middle School Students (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study examined the effect of the Teaching Games for Understanding (TGfU) model on the student active engagement and basketball learning outcomes. A quantitative quasi-experimental with a pretest–posttest control group design was applied. The sample consisted of 64 eighth-grade students, divided into a TGfU group (n = 32) and a conventional learning group (n = 32). The intervention was conducted over eight sessions. Data were collected using an active engagement observation sheet, basic skill tests (passing, dribbling, shooting), and the Game Performance Assessment Instrument (GPAI). Data were analyzed using ANCOVA with pre-test scores as covariates. The results showed that the TGfU group achieved significantly higher posttest scores than the conventional group in active engagement (F = 28.60; p 0.001), passing (F = 14.10; p 0.001), dribbling (F = 10.92; p = 0.002), shooting (F = 16.80; p 0.001), and GPAI (F = 24.50; p 0.001). This study concludes that TGfU is effective for improving learning outcomes.